Lingkungan Kerja Memediasi Motivasi Kerja terhadap Kinerja Guru SMK Ma’arif NU Bobotsari - Renita Renita; Dyah Supriatin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of work motivation on teacher performance by considering the mediation role of the work environment. The problems raised are uneven work motivation and several aspects of the work environment that do not support teacher performance at SMK Ma'arif NU Bobotsari. This study uses a quantitative method with the Partial Least Square (PLS-SEM) analysis technique. The population and sample in this study were all 78 teachers. The data collection method used a questionnaire. The results of the study showed that work motivation had a positive and significant effect on the performance of SMK Ma'arif NU Bobotsari teachers, work motivation had a positive and significant effect on the work environment of SMK Ma'arif NU Bobotsari teachers, the work environment had a positive and significant effect on the performance of SMK Ma'arif NU Bobotsari teachers, and the work environment was able to mediate work motivation on the performance of SMK Ma'arif NU Bobotsari teachers. These findings indicate that creating a conducive work environment can increase work motivation on the performance of SMK Ma'arif NU Bobotsari teachers. The result of the R-square calculation is only 39.3% which is still in the moderate category and means that there are still 61% of other variables that affect performance.